2009
DOI: 10.1111/j.1758-2229.2009.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Unique distribution of deep groundwater bacteria constrained by geological setting

Abstract: We collected groundwater samples at depths of up to 482 m from three boreholes drilled into sedimentary rock within two formations in Hokkaido, Japan. The prokaryotic community in each subsurface groundwater sample was analysed by microscopic counts and cloning-sequencing the 16S rRNA genes. On total direct counts, there were between 4.61 × 10(4) and 5.06 × 10(6) prokaryote cells ml(-1) in the samples, which is similar to the numbers observed at the marine subsurface. However, the vertical distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…Halobacteriales, comprised of 99.7 % Haloarcula, which inhabit environments with high concentrations of sodium, and Methanobacteriales, comprised of 97.4 % Methanothermobacter, a strict anoxic methane producer, were dominant members after the torrential rainfall. Increasing in abundance of such archaea can be supported by the finding that archaeal abundance increased with depth in both terrestrial (Kato et al, 2009) and marine (Lipp et al, 2008, Inagaki et al, 2015 subsurface environments. Deep groundwater in the study area contained high concentrations of Na + , from 14.3 to 14.6 mg L −1 (n = 13), while these were 5.3 to 7.8 mg L −1 (n = 33) in groundwater at SP-0 m and GW-42 m (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Halobacteriales, comprised of 99.7 % Haloarcula, which inhabit environments with high concentrations of sodium, and Methanobacteriales, comprised of 97.4 % Methanothermobacter, a strict anoxic methane producer, were dominant members after the torrential rainfall. Increasing in abundance of such archaea can be supported by the finding that archaeal abundance increased with depth in both terrestrial (Kato et al, 2009) and marine (Lipp et al, 2008, Inagaki et al, 2015 subsurface environments. Deep groundwater in the study area contained high concentrations of Na + , from 14.3 to 14.6 mg L −1 (n = 13), while these were 5.3 to 7.8 mg L −1 (n = 33) in groundwater at SP-0 m and GW-42 m (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…The communities are highly diverse, with genomic representation of 29 phyla, 13 of which currently lack cultivated representatives and were missed in prior 16S rRNA gene surveys of this site (Shimizu et al , 2006; Kato et al , 2009). Even the genomes from organisms affiliated with relatively well-studied phyla were phylogenetically novel, as over 120 genome bins could not be taxonomically placed beyond the family level (Supplementary Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…The URL is situated above Neogene rocks consisting of marine sandstones, mudstones and shales (Hama et al , 2007). Previous microbiological studies at Horonobe URL found a diversity of Proteobacteria and methanogens inhabiting the groundwater, as determined by sequencing of 16S ribosomal RNA (rRNA) gene libraries (Shimizu et al , 2006; Kato et al , 2009). Laboratory studies using rock samples collected from 200 m below ground surface and inoculated with Pseudomonas denitrificans supported the development of biofilm communities at in situ groundwater conditions (Harrison et al , 2011; Sakurai and Yoshikawa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Karst aquifer modification can be affected by external mechanisms like climate change that alter the flux of meteoric water into the system (see, e.g., Loáiciga et al, 2000;Loáiciga, 2009), or from internal processes like chemical reactions and microbial activity (see, e.g., Engel et al, 2004). Although microbes have been shown to affect water quality and biogeochemical and ecosystem-level processes in other types of aquifers (Griebler and Lueders, 2009;Kato et al, 2009;Stein et al, 2010;Smith et al, 2011), there has been limited research to define microbial activities that affect aquifer karstification.…”
Section: Introductionmentioning
confidence: 99%